MicroRNAs associated with initiation and progression of colonic polyp: A feasibility study. (January 2015) - Aslam, Muhammad Imran; Hussein, Samir; West, Kevin; Singh, Baljit; Jameson, John Stuart; Pringle, James Howard
Abstract: Introduction : Colorectal cancer is the third most common neoplasm worldwide. The sequential progression of colorectal cancer from adenoma to carcinoma highlights that opportunities exist to alter the natural course of disease progression. The aim of this study was to characterize the expression levels of microRNAs linked to development and progression of colorectal neoplasia.Patient, Design, Patients & Methods : MicroRNA expression signature was developed for RNA extracted from freshly frozen tumour and adjacent normal tissue ( n = 5). Based on differential expression and literature search, hsa-miR-135b was selected for further characterisation in different types of colonic polyps and cancer tissue. Formalin Fixed Paraffin Embedded tissue were studied for miRNA expression, KRAS, BRAF, PIK3CA mutations, and immuno-histochemistry for APC and p53 proteins for normal colon ( n = 11), hyperplastic polyps ( n = 11), high grade adenomas ( n = 10), low grade adenomas ( n = 34) and adenocarcinoma ( n = 13).Results : CRC tissue had significantly higher expression levels of hsa-miR-135b ( p = 0.0017) than their adjacent paired normal tissues (mean increase = 8.90 fold, 95% CI = 2.98–26.50). Linear trend analysis showed a progressive increase in expression level of hsa-miR-135b across normal epithelium, low grade adenomas, high grade adenomas and carcinomas ( p = 0.0007, R squared 0.16, slope −0.35). KRAS mutant colonic polyps and cancer tissue had significantly higher (3.04 fold, 95% CI = 1.23–7.46) expression levels of hsa-miR-135b compared to polyps and cancers with non mutant KRAS gene ( p = 0.001). Whereas, hsa-miR-135b expression levels were significantly lower in colonic polyp and cancer tissue stained positively for APC proteins ( p < 0.001).Conclusion : There is a progressive increase in expression levels of hsa-miR-135b correlating with the sequential progression of normal epithelium to adenoma and carcinoma. Expression levels of hsa-miR-135b correlate with expression of APC proteins in colorectal tissue suggesting its role in tumour initiation.Highlights : This study highlights the role of tissue microRNAs for their role in the development of colorectal carcinoma. Identification of tissue specific microRNAs will help is designing microRNAs based gene therapies to control the development and progression of colonic neoplasia. Highlights: There is a progressive increase in expression levels of miR-135b. This correlates with the sequential progression of normal epithelium to adenoma and carcinoma. Loss of APC gene is associated with tumour initiation. Expression levels of hsa-miR-135b correlate with expression of APC protein.